2020
DOI: 10.30919/esmm5f810
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Finite Element Simulation on the Interfacial Bonding Performance of Functionally Gradient Concrete

Abstract: To study the bonding shear performance of the casting interface in the functionally gradient concrete (FGC), a multiphase mesoscopic finite element modeling method was proposed to simulate a sandwich FGC specimen with the normal weight concrete (NWC) cast on the hardened ceramsite lightweight aggregate concrete (LWAC) layer. Four kinds of phases are considered during modeling: coarse aggregates, mortar substrate, interface transition zone (ITZ) between the mortar and coarse aggregates, and the casting interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[8][9][10][11] And as solid lubricating materials, they demonstrate unique advantages over liquid and gas lubricants, and can be used under the sliding condition of high vacuum, ultra-high temperature, ultra-low temperature, etc. [12,13] As is well known, the interfacial compatibility between fillers and matrix has influenced the compressive performance of composites, [14] and many researchers have focused on the surface modification of fillers. Liang et al reported that the sorbitol modified fluorine-acrylic emulsion has good interfacial compatibility with sulphoaluminate.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] And as solid lubricating materials, they demonstrate unique advantages over liquid and gas lubricants, and can be used under the sliding condition of high vacuum, ultra-high temperature, ultra-low temperature, etc. [12,13] As is well known, the interfacial compatibility between fillers and matrix has influenced the compressive performance of composites, [14] and many researchers have focused on the surface modification of fillers. Liang et al reported that the sorbitol modified fluorine-acrylic emulsion has good interfacial compatibility with sulphoaluminate.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are four main ways to model an ITZ of concrete. The first method is to treat the concrete aggregates as a polygon and to extend around the polygon [4,5]. However, when the particles have sharp corners, this method overestimates the range of the ITZ.…”
Section: Introductionmentioning
confidence: 99%